Home‐care providers as collaborators in commissioning arrangements for older people. (1st October 2020) - Davies, Karen; Dalgarno, Elizabeth; Angel, Colin; Davies, Susan; Hughes, Jane; Chester, Helen; Jasper, Rowan; Roberts, Amy; Challis, David
Abstract: In England, care to support people living at home is largely commissioned by local authorities (statutory organisations with responsibility for social care in specific localities) from non‐statutory home‐care providers (for‐profit, not‐for‐profit, voluntary). This paper explores how managers of these services perceive commissioning arrangements and their impact on home‐care providers, the care workforce and service users. Little formal research of providers' experiences of working with local authorities in a commissioning model is available. A qualitative study employed semi‐structured telephone interviews with 20 managers of for‐profit home‐care providers from 10 selected local authority areas in England. Data were analysed using thematic analysis to identify main and subsidiary themes. Home‐care providers reported operating in a complex and changeable partnership with commissioners, characterised by: (a) relationships ranging from transactional to collaborative, (b) providers expressing a strong sense of public service motivation, (c) commissioning practices that were complex to negotiate, time‐consuming and overly prescriptive, (d) frequent changes in commissioning practices and a perceived lack of strategic planning, which were reported as contributing to uncertainty and tension for providers and confusion for service users. Attempting to operate a market model with tightly prescribed contracts is likely to be unsustainable. An alternative approach based on a collaborative model of joint responsibility for providing home care is recommended drawing on a conceptual framework of principal–steward relationships in contracting.